The Relationship Between Airline Cargo Carriers and Port Health Authorities - Thakker, Amit (2012)
Over the past few years, UK has seen a steep increase in the demand for imported perishable items, particularly food such as meat and fresh produce. Reports have suggested that the ratio of imports to exports of perishable items in the UK is at 2:1. Significant amounts of these imports are from countries outside the European Union. Many environment and health related events in the last decade, such as the Foot & Mouth disease epidemic in 2001, followed by numerous instances of food contamination in imports from third countries and similar events resulted in Governments heavily regulating international trade in environment and health sector.